Use of bessel polynomials for solving differential difference equations. Issue 1 (2nd January 2019) - Elahi, Zaffer; Akram, Ghazala; Siddiqi, Shahid S.
Abstract: In this paper, the linear differential difference equation subject to the mixed conditions has been solved numerically using Bessel polynomials. The solution is obtained in terms of Bessel polynomials. In addition, the accuracy and error analysis of the method are considered using residual function. Some examples have also been considered to examine the applicability and reliability of the method.